2018
DOI: 10.1177/0040517518803774
|View full text |Cite
|
Sign up to set email alerts
|

Stable super-hydrophobic lauryl methacrylate film fabrication on the surface of cotton fabrics in plasma-enhanced chemical vapor deposition with different duty cycles

Abstract: In this paper, stable super-hydrophobic lauryl methacrylate (LMA) film on the surface of cotton fabrics was fabricated by a simple process of pulsed plasma-enhanced chemical vapor deposition (PECVD) with different duty cycles. The influence of duty cycles on the surface structure and properties of cotton fabrics was analyzed after a series of measurements. The results showed that water contact angles (WCAs) of samples were inversely proportional to the duty cycle values and exhibited the highest WCA (162°) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Table 9 provides a categorized list of the main precursors used for polymer film growth, distinguishing between monomeric and non-monomeric substances. Methyl methacrylate [113] ; styrene [263] ; 2-methyl-1,3-butadiene (isoprene) [264] ; Vinyltriethoxysilane [265] Aromatic monomers Pyrrole [266] ; Thiophene [267] ; Aniline [268] Acrylate monomers 1H,1H,2H,2H-perfluorododecyl acrylate (PFDA) [269] ; Dodecylacrylate (DOCA) [269] ; Lauryl methacrylate (LMA) [270] Fluorinated monomers (Carbon-fluorine bonds)…”
Section: From Molecular Precursors In the Gas Phase To The Synthesis ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 9 provides a categorized list of the main precursors used for polymer film growth, distinguishing between monomeric and non-monomeric substances. Methyl methacrylate [113] ; styrene [263] ; 2-methyl-1,3-butadiene (isoprene) [264] ; Vinyltriethoxysilane [265] Aromatic monomers Pyrrole [266] ; Thiophene [267] ; Aniline [268] Acrylate monomers 1H,1H,2H,2H-perfluorododecyl acrylate (PFDA) [269] ; Dodecylacrylate (DOCA) [269] ; Lauryl methacrylate (LMA) [270] Fluorinated monomers (Carbon-fluorine bonds)…”
Section: From Molecular Precursors In the Gas Phase To The Synthesis ...mentioning
confidence: 99%
“…Methyl methacrylate [113]; styrene [262]; 2-methyl-1,3-butadiene (isoprene) [263]; Vinyltriethoxysilane [264] Aromatic monomers Pyrrole [265]; Thiophene [266]; Aniline [267] Acrylate monomers 1H,1H,2H,2H-perfluorododecyl acrylate (PFDA) [268]; Dodecylacrylate (DOCA) [268]; Lauryl methacrylate (LMA) [269] Fluorinated monomers (Carbon-fluorine bonds)…”
Section: Monomersmentioning
confidence: 99%
“…A hydrophobic/oleophilic cotton textile is developed by plasma polymerization of PDMS solution, which is a green and economical source of Si-based polymers for plasma. Cotton is a low-cost material with excellent flexibility and can be considered as a suitable substrate to fit working conditions [30,31]. Furthermore, cotton surface with its hydrophilic hydroxyl groups can be easily functionalized by physical or chemical treatments and used for oil-water separation [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In our past research, we used dodecyl methacrylate (LMA) as the monomer via the plasma-enhanced chemical vapor deposition (PECVD) method [21][22][23] and the immersion-plasma-induced crosslinking method [24], respectively, to successfully prepare durable superhydrophobic cotton fabric, and it was found that the superhydrophobicity of cotton fabric made by the immersion-plasma-induced crosslinking method had better durability. Therefore, in this paper, cotton, PET, thermoplastic polyurethane (TPU) and polyamides-6 (PA6) fabrics were treated by LMA and low-voltage capacitively coupled discharge plasma (LP-CCP) via the immersion-plasma-induced crosslinking method, and the performances of the cotton and PET fabrics were compared to probe the influence of the presence of hydroxyl groups on the properties of LMA-coated fabrics.…”
Section: Introductionmentioning
confidence: 99%